2010
DOI: 10.1111/j.1365-2753.2009.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

A new scale to measure family members' perception of community health care services for persons with Huntington disease

Abstract: Rationale, Aims, and Objectives Huntington Disease (HD) is a progressive genetic brain disease leading to disruptive cognitive, behavioral, and physical impairments. Persons with the condition and their caregivers need appropriate and accessible health care services to help them manage the disease adequately. The purpose of this study was to evaluate the psychometric properties of a new scale that measures family members' perception of community health care services (CHCS) for persons with HD. Methods A meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…17,18 Recent psychometric research utilizing factor analysis revealed three main areas of concern for HD carers: individualized care for their relative, availability of community resources and HD knowledge in healthcare professionals. 10,19 As the first point of contact inthe Canadian healthcare system, primary care plays a central role for families affected by genetic illness, including HD. Information about genetic tests is increasingly available to patients via the internet, popular media and direct-toconsumer marketing, and patients are likely to turn to their primary care providers (PCPs) for advice in making informed decisions about genetic services.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Recent psychometric research utilizing factor analysis revealed three main areas of concern for HD carers: individualized care for their relative, availability of community resources and HD knowledge in healthcare professionals. 10,19 As the first point of contact inthe Canadian healthcare system, primary care plays a central role for families affected by genetic illness, including HD. Information about genetic tests is increasingly available to patients via the internet, popular media and direct-toconsumer marketing, and patients are likely to turn to their primary care providers (PCPs) for advice in making informed decisions about genetic services.…”
Section: Introductionmentioning
confidence: 99%